Innovation and reform in teacher training curricula in democratic times in Brazil (1990/2000) - Marcia Serra Ferreira; Maria do Carmo Martins (Arizona State University, 2019)
In this article, the notions of curricular innovation and theory-practice relationship, presented in academic texts and official documents for teacher training in Brazil, are problematized. The analysis makes possible the emergence of a curricular history of the present, focusing on the educational reforms of the 1990/2000. In dialogue with Michel Foucault and Thomas Popkewitz, pedagogic discourse elements gain duration and power and express a system of reasoning that creates rules and truthsfor this formation in the country. It is inscribed as a contribution to the theoretical-methodological debate on educational reforms in democratic times. It also assumes the relation between knowledge and power, in these recent reformist waves, as capable of structuring our perceptions and social practices.